أستخلاص وتنقية حامض اللايبوتكوك جزئيا من بكتريا Enterococcus faecalis المعزولة محليا - شاكر خمائل لطفي; فليح مي طالب; عبد الكريم لينة (Al-Nahrain Journal of Science, 2018)
Fourty seven Enterococcus faecalis isolates were obtained from 300 samples (100 Stool sample, 100 Urine sample, 100 Skin infection sample) at percentages of 28, 15 and 4% respectively. Lipotechoic acid (LTA) was extracted from the isolate Enterococcus faecalis U12.. Extraction was carried out using hot phenol and LTA was partially purified by gel filtration chromatography using Sepharose CL- 4B (1.4×65 cm). The peak of LTA was occupied the fractions from 16-27, the concentration of phosphate was 45.4 μmol ⁄g and the protein percentage was 1.2% of the lyophilized LTA. The sensitizing activity of extracted LTA was 62.5 μg ⁄ml and 15.6 μg ⁄ml for partially purified LTA, with no sensitizing activity for dLTA.